2020
DOI: 10.1002/cbdv.202000564
|View full text |Cite
|
Sign up to set email alerts
|

Profile of Terpenoid Compounds Mediating a Plant‐Herbivore Interaction: Screening by Static Headspace Solid‐Phase Microextraction‐Gas Chromatography/Q‐ToF Mass Spectrometry

Abstract: Conotrachelus dimidiatus (Coleoptera: Curculionidae) interacts with immature guava fruits (Psidium guajava L.) for feed, sleep, mate and oviposit. Determination of the volatile organic compounds (VOCs) emitted by the insect and immature fruits can help improve understanding of plant-insect and intraspecific insect interactions between females and males of C. dimidiatus. Daytime fruit setting emissions of immature guava consist mainly of limonene, caryophyllene, and aromadendrene. In addition to the host's vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Aromadendrene 2 ( 5 ) was illustrated in several species of the Myrtaceae family, such as Eucalyptus sp. [ 32 , 45 ], Psidium guajava [ 46 ], and Lophomyrtus sp. [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aromadendrene 2 ( 5 ) was illustrated in several species of the Myrtaceae family, such as Eucalyptus sp. [ 32 , 45 ], Psidium guajava [ 46 ], and Lophomyrtus sp. [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that β-curcumene and α-bisabolol, the majority constituents of the EOs of Curcuma sp. (Zingiberaceae) and Plinia cerrocampanensis (Myrtaceae), respectively, have anti- H. pylori activities [ 46 , 47 , 49 ]. In addition, Brehm-Stecher & Johnson [ 66 ] described that bisabolol is able to increase bacterial wall permeability and, consequently, susceptibility to antibiotics of clinical importance, suggesting a possible mechanism for its activity.…”
Section: Discussionmentioning
confidence: 99%